Self-injury Remaja Ditinjau dari Konsep Dirinya - Muslimah Zahro Romas (Jurnal Psikologi, 2012)
Objective of this research is to understand the relationship between selfconcept and self-injury behavior among adolescents. Adolescents with positive selfconcept were able to maintain their emotion when they received critics. Therefore they would be less likely to do self-injury. Adolescents with negative self-concept, on the other hand, were unable to maintain their emotion when they received critics. Therefore they would be more likely to do self-injury. Eighty eight students aged 1618 years old participated in this study. In order to measure adolescent's self concept, the Self-concept Scale was used. Range of the Self-concept Scale discrimination index was about .367-.643, and the reliability coefficient was .772. The Self-injury Scale was also used to measure the dependent variable. Range of the discrimination index of the Self-injury Scale was about .236- 631, and the reliability coefficient was .792. The hypothesis examination revealed rxy- -.484, p = .000 (p <.01). There was negative relationship between self-concept and self-injury behavior. The effective contribution of the independent variable in predicting the dependent variable was about 23.4%. It was about 76.6% variables out side this research would be likely to predict the dependent variable. The self-report method on describing the self-injury behavior was likely to be the phmary reason for middle level of the effective contribution. Respondent’s answer might not be accurate.